Gender pada Usaha Pengolahan Ikan di PT. Jaya Bitung Mandiri di Kelurahan Aertembaga Satu Kecamatan Aertembaga Kota Bitung - Walukow, Gabryela M.; Pangemanan, Jeannette F.; Aling, Djuwita R.R.; Andaki, Jardie A.; Durand, Swenekhe S.; Rantung, Steelma V. (AKULTURASI, 2024)
Abstract Economic fisheries development is an activity that utilizes natural resources which is directed towards the main targets of meeting food needs, increasing employment opportunities, increasing foreign exchange earnings, and maintaining a sustainable business and environment. The development of the fisheries and marine sector as part of national development aims to ensure that every fisheries and marine activity can be carried out by the Indonesian people, both production activities and marketing processing. Gender is the characteristics and behavior attributed to men and women which are formed socially and culturally. Gender can be defined as a situation where individuals who are born biologically as male and female then acquire social characteristics as male and female through the attributes of masculinity and femininity which are often supported by values or systems and symbols in the society concerned. The basic method used in this research is the data collection technique using a purposive sampling method which is carried out with several considerations so that the data obtained will be more precise. The sample interviewed consisted of 22 employees from the population determined at each processing unit. Data collection was carried out through observation, interviews, questionnaires and documentation, both photo documentation and taking written documents at PT. Jaya Bitung Mandiri. The analysis used is quantitative descriptive analysis and qualitative descriptive analysis. Based on the results of the research and discussion, it can be concluded: 1) there are gender differences in each fish processing business at PT. Jaya Bitung Mandiri Bitung City starting from the sorting, processing, tally, cold storage section; 2) reproductive activities in the processing business between men and women at PT. Jaya Bitung Mandiri has the same percentage of 50% of each task and responsibility according to existing abilities and skills.  Keywords : gender; fish processing business; fish factory workers   Abstrak Ekonomi pembangunan perikanan adalah kegiatan pemanfaatan sumberdaya alam yang diarahkan dengan sasaran utama pencukupan kebutuhan pangan, peningkatan kesempatan kerja, peningkatan pendapatan devisa, dan pemeliharaan usaha serta lingkungan yang lestari. Pembangunan sektor perikanan dan kelautan sebagai bagian dari pembangunan nasional bertujuan untuk mengusahakan agar setiap kegiatan perikanan dan kelautan dapat dilakukan oleh bangsa Indonesia baik kegiatan produksi, pengolahan maupun pemasaran. Gender adalah sifat dan perilaku yang dilekatkan pada laki-laki dan perempuan yang dibentuk secara sosial maupun budaya. Gender dapat didefinisikan sebagai keadaan dimana individu yang lahir secara biologis sebagai laki–laki dan perempuan yang kemudian memperoleh pencirian sosial sebagai laki-laki dan perempuan melalui atribut – atribut maskulinitas dan feminitas yang sering didukung oleh nilai-nilai atau sistem dan simbol di masyarakat yang bersangkutan. Metode yang digunakan dalam penelitian ini yaitu dengan teknik pengambilan data adalah dengan menggunakan metode purposive sampling yang dilakukan dengan beberapa pertimbangan agar data yang diperoleh akan lebih tepat. Sampel yang di wawancarai berjumlah 22 karyawan dari populasi yang ditentukan pada setiap unit pengolahan. Pengumpulan data dilakukan melalui obeservasi, wawancara, kuesioner, dan dokumentasi baik itu dokumentasi foto maupun pengambilan dokumen tertulis pada PT. Jaya Bitung Mandiri. Analisis yang digunakan adalah analisis deskriptif kuantitatif dan analisis deskriptif kualitatif. Berdasarkan hasil   penelitian   dan   pembahasan   dapat   disimpulkan: 1) terdapat perbedaan gender pada setiap usaha pengolahan ikan di PT. Jaya Bitung Mandiri Kota Bitung mulai dari bagian sortir, processing, tally, cold storage; 2) kegiatan reproduktif usaha pengolahan antara laki-laki dan perempuan di PT. Jaya Bitung Mandiri memiliki Persentase yang sama 50% dari tugas dan tanggung jawab masing-masing sesuai dengan kemampuan dan keterampilan yang ada. Kata Kunci : gender; usaha pengolahan ikan; pekerja pabrik ikan